Modus of categoricity in the system of expressive syntactic means in Eastern Slavonic languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the modus of categoricity as an expressive syntactic means is studied. The author suggests that the pragmatic direction brings together the categoricity and expressivity, makes it one of the most important means of verbal influence. The causes of  categoricity intensification, its genres and means of its defining are investigated.
Keywords: addressee; expressio; emotional condition of the speaker; categoricity; modus meaning; categoricity and communication shade of meaning